ANALISIS KESTABILAN DAN BIFURKASI PADA MODEL MATEMATIKA TINGKAT PENGANGGURAN PADA MASA PANDEMI COVID-19 - Bohari, Nurul Aulia; Toaha, Syamsuddin; Kasbawati, Kasbawati (Universitas Cokroaminoto Palopo, 2022)
Covid-19 is a type of virus from the Coronaviridae which has implications for infectious and deadly diseases that attack mammals such as humans in the respiratory tract to the lungs. In the conditions of the outbreak of the Covid-19 pandemic, it turns out that there are many impacts, mainly in the Indonesian economic sector, for example unemployment, with the spread of the Covid-19 virus in Indonesia to date, it is possible that the unemployment rate in Indonesia will increase. The purpose of this study is to see how the unemployment rate during the Covid-19 pandemic is taking into account several compartments, namely susceptible, unemployed, employed, reduction, and lead, showing a sensitivity analysis to determine the parameters that affect the basic reproduction number , and bifurcation analysis. The results obtained from the sensitivity analysis, which found a parameter relationship with which could increase and decrease the value of , and the bifurcation analysis showed the effect of changes in the stability of the equilibrium point due to changes in the value of the parameter . model simulation shows the unemployment rate during the Covid 19 pandemic and to show the effect of the governments policy rate ( on unemployment during the Covid 19 pandemic.